An introduction to evidence-based medicine - Guyatt, Gordon (Henry Stewart Talks, 2018)
Making evidence-based clinical decisions, First principle: nature of Evidence, Second principle: hierarchies of evidence, Third principle: values and preferences, Evidence-based clinicians, Interpreting the evidence